Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1007/bf00266031
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic changes in insulin-induced hypoglycaemia in normal man

Abstract: Haemodynamic variables (plasma volume, heart rate, blood pressure, cardiac output, stroke volume, pulmonary tissue volume, total peripheral vascular resistance, hepato-splanchnic vascular resistance, lower extremity vascular resistance and plasma catecholamines) were measured before and after insulin-induced hypoglycaemia in seven healthy men. Plasma volume decreased significantly at the nadir of glucose (mean decrease 222 +/- 41 ml) and subsequently increased to pre-hypoglycaemic values within 30 min. Cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 20 publications
6
69
1
Order By: Relevance
“…To verify the safety of OHA treatment, blood glucose profiles should be performed in Type 2 diabetic patients; at least a late afternoon value should be regularly checked. The risk of repeated low glucose values must be carefully considered in an older population potentially affected by atherosclerotic lesions, to avoid the iatrogenic effects of neuroglycopoenia and of catecholamine-mediated vascular damage [2][3][4][5][6][7][8][9]. In this light, the fasting and postprandial glycaemic targets of the European Policy Group [1] should be considered in an integrate view, and not separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the safety of OHA treatment, blood glucose profiles should be performed in Type 2 diabetic patients; at least a late afternoon value should be regularly checked. The risk of repeated low glucose values must be carefully considered in an older population potentially affected by atherosclerotic lesions, to avoid the iatrogenic effects of neuroglycopoenia and of catecholamine-mediated vascular damage [2][3][4][5][6][7][8][9]. In this light, the fasting and postprandial glycaemic targets of the European Policy Group [1] should be considered in an integrate view, and not separately.…”
Section: Discussionmentioning
confidence: 99%
“…The 4.4 mmol/1 limit is due to the fact that lower concentrations could be dangerous in an older population frequently affected by vasculopathy, since values greater than the limits of chemical hypoglycaemia cause neurological abnormalities due to neuroglycopoenia and activate adrenergic glucose counterregulation [2]. The latter phenomenon is potentially dangerous as it can precipitate vascular complications of the disease owing to haemorheological, haemodynamic and haemostatic changes, as it has been described during insulin-induced hypoglycaemia [3][4][5][6][7][8][9]. Since one of the main targets of Type 2 diabetes treatment is the prevention of angiopathy, it is particularly important to avoid low blood glucose concentrations.…”
mentioning
confidence: 99%
“…In one hypoglycemia clamp study (plasma glucose 3.0 mmol/L [54 mg/dL]) in participants without diabetes, a 12-fold increase in plasma epinephrine concentration was observed that was associated with increased heart rate and cardiac stroke volume and decreased peripheral resistance (15). Acute hypoglycemia provokes a substantial rise in myocardial contractility (16) and cardiac output (17). These hemodynamic changes are accompanied by an increase in elasticity of large blood vessels and a fall in central arterial pressure, with both measures being diminished in young men with type 1 diabetes of long duration (.15 years) in whom arterial stiffness has developed (18).…”
Section: Cardiovascular Effects Of Hypoglycemiamentioning
confidence: 99%
“…8 -10 These observations have supported the suggestion that the tachycardia and the rise in blood pressure observed during a hypoglycemic episode might destabilize an atherosclerotic plaque. 11 These hemodynamic changes, the increased myocardial work, and hypoglycemia-induced increases in platelet aggregation, platelet activity, [12][13][14] and hematocrit 15,16 may precipitate cardiac and cerebral ischemic events in patients at high risk of cardiovascular disease. 17 Support for this possibility comes from a number of small studies and case reports.…”
mentioning
confidence: 99%